PROFESSIONAL AND ETHICAL DILEMMAS IN SOFTWARE ENGINEERING. - Berenbach, Brian; Broy, Manfred (Computer (00189162), 2009)
This article discusses the use of the code of conduct for the Institute of Electrical & Electronics Engineers Inc. (IEEE) to address a series of ethical dilemmas in software engineering. The ethical dilemmas addressed in this article center around the challenges posed by team work to the establishment of individual ethical responsibility. Issues relating to the release of software that does not meet standards outlined in sales contracts are noted. The role of risk assessment and diligence in dealing with issues relating to dysfunctional or inadequate software is addressed. Issues faced by engineers who have taken assignments that are undermined by poor project design and management are framed in terms of the IEEE ethics codes.